Cardiovascular risk factors during cancer treatment: prevalence, incidence and prognostic relevance. (25th November 2020) - Caro Codon, J; Lopez-Fernandez, T; Alvarez-Ortega, C; Zamora Aunon, P; Rodriguez Rodriguez, I; Gomez Prieto, P; Buno Soto, A; Canales Albendea, M; Feliu Batlle, J; Rodriguez Fraga, O; Martinez Monzonis, A; Gonzalez-Costello, J; et al.
Abstract: Background: The actual usefulness of CV risk factor assessment in the prognostic evaluation of cancer patients treated with cardiotoxic treatment remains largely unknown. Design: Prospective multicenter study in patients scheduled to receive anticancer therapy related with moderate/high cardiotoxic risk. Methods: A total of 1324 patients underwent follow-up in a dedicated cardio-oncology clinic from April 2012 to October 2017. Special care was given to the identification and control of CV risk factors. Clinical data, blood samples and echocardiographic parameters were prospectively collected according to protocol, at baseline before cancer therapy and then at 3 weeks, 3 months, 6 months, 1 year, 1.5 years and 2 years after initiation of cancer therapy. Results: At baseline, 893 patients (67.4%) presented at least 1 risk factor, with a significant number of patients newly diagnosed during follow-up. Individual risk factors were not related with worse prognosis during a 2-year follow-up. However, a higher Systemic Coronary Risk Estimation (SCORE) was significantly associated with higher rates of severe cardiotoxicity and all-cause mortality [HR 1.79 (95% CI 1.16–2.76) for SCORE 5–9 and HR 4.90 (95% CI 2.44–9.82) for SCORE ≥10 when compared with patients with lower SCORE (0–4)]. Conclusions: This large cohort of patients treated with a potentially cardiotoxic regimen showed a significant prevalence of CV risk factors at baseline and significant incidence during follow-up. Baseline cardiovascular risk assessment using SCORE predicted severe cardiotoxicity and all-cause mortality. Therefore, its use should be recommended in the evaluation of cancer patients. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): This study was partially funded by the Fondo Investigaciones Sanitarias (Spain), Centro de Investigaciόn Biomédica en Red Cardiovascular CIBER-CV (Spain)